2022
DOI: 10.1186/s13567-022-01073-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pathogenesis of peste des petits ruminants virus strains of difference virulence

Abstract: Peste des petits ruminants (PPR) is an acute disease of small ruminants caused by a morbillivirus. Clinical observation of the disease in the field revealed that several species of small ruminants are affected to varying degrees. This difference in disease-related effects could depend either on the host or on the virulence of the virus strain. A previous study highlighted the difference in virulence between two strains of PPRV used to infect Saanen goats. For this breed, PPRV Morocco 2008 strain (MA08) was hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…Transient lymphopaenia is induced by infection of immune cells via its receptor CD150 (SLAM). Previously, PPRV-specific RNA has been detected in whole blood, WBC or serum of experimentally inoculated goats that mostly peaked at the end of the first week post-inoculation [17,18,20,21,25]. In our study, we quantified the percentage of infected lymphocytes based on the expression of EGFP and confirmed peak infection at 7-8 dpi.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Transient lymphopaenia is induced by infection of immune cells via its receptor CD150 (SLAM). Previously, PPRV-specific RNA has been detected in whole blood, WBC or serum of experimentally inoculated goats that mostly peaked at the end of the first week post-inoculation [17,18,20,21,25]. In our study, we quantified the percentage of infected lymphocytes based on the expression of EGFP and confirmed peak infection at 7-8 dpi.…”
Section: Discussionsupporting
confidence: 77%
“…However, an early induction of PPRV-specific antibodies at the end of the first week post-infection does not necessarily prevent the animals from dying after a PPRV infection [16]. We measured an early humoral response in both study groups; the response was slightly faster in rPPRV/Tbilisi-EGFP-inoculated animals as compared to vaccine virus-inoculated animals, confirming observations of a faster and stronger immune response in animals that have been inoculated with a more virulent PPRV strain than with a less severe or vaccine strain [16,25]. In contrast, Rajak et al observed a delayed onset of PPRV-specific and bystander antibodies in goats experiencing severe clinical symptoms, suggesting that the immune system may be impaired during PPRV infection [15].…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations